Assessment of weather and atmospheric pollution as a co-factor in the spread of SARS-CoV-2 - Gonçalves, José; Koritnik, Tom; Paragi, Metka (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: COVID-19 is a persistent and ongoing global pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Non-anthropogenic factors, such as weather conditions and air quality are possible predictors of respiratory diseases, such as COVID-19. Weather conditions may also be a direct cause of biological interactions between SARS-CoV-2 and humans and vary widely between regions. The course of an epidemic is determined by several factors, including demographic and environmental parameters, many of which have an unknown correlation with COVID-19. The goal of this study is to access the influence of ground surface particulate matter and weather parameters on the dissemination of COVID-19 in Ljubljana, Slovenia. Methods: Spearman rank correlation was used to investigate the association between new daily COVID-19 cases and weather data. Results: The current study has found correlations between weather variables and PM particles with new cases of COVID-19. Conclusions: The correlations observed are highly dependent on the local policies that were in force during the period under study. The interaction between weather conditions and human behaviour may also be an important factor in understanding the relationship between weather and the spread of COVID -19.